2013
DOI: 10.1371/journal.pone.0061179
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Selected Physical and Mechanical Properties of a Telechelic Polybenzoxazine by Molecular Simulation

Abstract: Molecular simulation is becoming an important tool for both understanding polymeric structures and predicting their physical and mechanical properties. In this study, temperature ramped molecular dynamics simulations are used to predict two physical properties (i.e., glass transition temperature and thermal degradation temperature) of a previously synthesised and published telechelic benzoxazine. Plots of simulated density versus temperature show decreases in density within the same temperature range as experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Therefore, it has been extensively applied to the simulation of different cross-linked polymers in order to study their thermomechanical properties. Kim and Mattice explored the conformational distribution of single chains and the structure of thin benzoxazine films. The analysis of the supramolecular network structures revealed the role of hydrogen bonding in the polymerization process and the properties of the polybenzoxazines. In particular, the predicted thermomechanical properties of polybenzoxazines showed an excellent agreement with the experimental results, highlighting the ability of molecular simulations to accurately describe the properties of polybenzoxazines. , …”
Section: Introductionmentioning
confidence: 83%
“…Therefore, it has been extensively applied to the simulation of different cross-linked polymers in order to study their thermomechanical properties. Kim and Mattice explored the conformational distribution of single chains and the structure of thin benzoxazine films. The analysis of the supramolecular network structures revealed the role of hydrogen bonding in the polymerization process and the properties of the polybenzoxazines. In particular, the predicted thermomechanical properties of polybenzoxazines showed an excellent agreement with the experimental results, highlighting the ability of molecular simulations to accurately describe the properties of polybenzoxazines. , …”
Section: Introductionmentioning
confidence: 83%
“…shown that the COMPASS force field is capable of accurately predicting the elastic properties of organic and polymeric materials [33][34][35][36]. With the COMPASS force field, the solubility of lithium salts (organic and inorganic materials) found in the SEI layer was also calculated,…”
Section: Computational Proceduresmentioning
confidence: 99%
“…In general, PBzs emerged as a promising class of thermoset polymers exhibiting versatility in a wide range of applications including adhesives [ 9 , 10 , 11 , 12 , 13 , 14 ], flame resistant polymers [ 15 , 16 , 17 , 18 ], cathodic material in batteries [ 19 , 20 , 21 , 22 , 23 , 24 ], coatings [ 14 , 25 , 26 , 27 , 28 ], materials for aerospace applications [ 29 ], carbon dioxide adsorbent [ 30 , 31 , 32 , 33 , 34 ], detection of metal ions [ 35 , 36 , 37 , 38 ], 3D printing [ 39 ] and electronics [ 40 , 41 ]. Besides effective compatibilization with many polymers, they also offer notable properties such as good mechanical strength [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ], high thermal stability [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], flame retardance […”
Section: Introductionmentioning
confidence: 99%